Analisis Produksi dan Biaya Pengupasan Overburden Menggunakan Metode Simpleks di PT. Allied Indo Coal Jaya, Parambahan, Sawahlunto, Sumatera Barat - Resty Hardi; Adree Octova (Journals Mining Engineering : Bina Tambang, 2020)
Abstract. PT. Allied Indo Coal Jaya is one of the companies engaged in the coal mining business in the city of Sawahlunto with the status of the Mining Entrepreneurs Cooperation Agreement (PKP2B) in an area of 327.4 hectares. PT. Allied Indo Coal Jaya (PT. AICJ) has a constant production target every month with a target of 294,117.65 BCM / month to produce overburden. However, the realization of overburden excavation production in December did not reach the target of 175,708.73 BCM / month. In 1 fleet there is a loading device serving 3 to 5 unit so that there is a queue conveyance. This shows that the mismatch of loading and hauling equipment is not suitable so that the production and overburden stripping production costs are not optimal. Therefore it is necessary to plan the transportation needs and optimal costs for optimizing overburden production. To solve this, a more complex method is needed, using the Simplex method. Based on the Simplex Method, there are 10 units of dumptruck planning that were previously 13 units. then based on the application of the Linear Programming Method Simplex obtained optimal production obtained for overburden stripping of 277.37 BCM / hour with a production cost of 5.41 USD /BCM.